2008
DOI: 10.1007/s12072-008-9061-6
|View full text |Cite
|
Sign up to set email alerts
|

Recent data on treatment of chronic hepatitis B with nucleos(t)ide analogues

Abstract: Forty years ago in 1967, Professor Blumberg discovered the Australian Antigen, later known as the hepatitis B surface antigen, and was awarded the Nobel Prize. This discovery enables the diagnosis of hepatitis B virus (HBV) infection and defines its epidemiology. Viral hepatitis B infection affects global health situation, and chronic hepatitis B (CHB) is particularly serious in the Asia-Pacific region. HBV vaccines created the first breakthrough in HBV prevention. Through universal HBV vaccination program for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 123 publications
0
53
0
1
Order By: Relevance
“…It has an excellent safety profile (Ayoub & Keeffe, 2008;Fung et al, 2008;Jacobson, 2006;Leung, 2008;Y F Liaw et al, 2008) and is the least expensive of all nucleoside analogs approved for the treatment of CHB (Dan, Aung, & Lim, 2008;Zoulim & Perrillo, 2008). It is effective in suppressing HBV DNA, normalizing ALT and HBeAg seroconversion (Dienstag et al, 1999;Fung et al, 2008;Lai et al, 1998;Y F Liaw et al, 2008;.…”
Section: Anti-viral Drug Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It has an excellent safety profile (Ayoub & Keeffe, 2008;Fung et al, 2008;Jacobson, 2006;Leung, 2008;Y F Liaw et al, 2008) and is the least expensive of all nucleoside analogs approved for the treatment of CHB (Dan, Aung, & Lim, 2008;Zoulim & Perrillo, 2008). It is effective in suppressing HBV DNA, normalizing ALT and HBeAg seroconversion (Dienstag et al, 1999;Fung et al, 2008;Lai et al, 1998;Y F Liaw et al, 2008;.…”
Section: Anti-viral Drug Treatmentmentioning
confidence: 99%
“…It is effective in suppressing HBV DNA, normalizing ALT and HBeAg seroconversion (Dienstag et al, 1999;Fung et al, 2008;Lai et al, 1998;Y F Liaw et al, 2008;. Previous studies showed that LVD led to significant histological improvement and reduction in the progression of liver fibrosis (Ayoub & Keeffe, 2008;Dienstag et al, 1999;Lai et al, 1998;Leung, 2008). Long-term LVD therapy reduces the risk of developing cirrhosis and HCC in precirrhotic/cirrhotic and non-cirrohotic patients (Y. F. Liaw et al, 2004;.…”
Section: Anti-viral Drug Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the yet unresolved CHB treatment issues is that the current recommendations and guidelines for CHB treatment exclude the groups of patients with lower HBV-DNA levels and patients with high HBV-DNA but normal ALT, who both still have a risk of progression to cirrhosis and HCC [18,[21][22][23]. In addition, most of the orally used nucleotide and nucleoside analogs for treatment of CHB carry variable risks of drug resistance [15,16,24]. Another issue of concern is the implementation of mass vaccination programs for HBV worldwide in children, which has resulted in the emergence of new HBsAg vaccine-escaped mutants of HBV [25].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the initial clinical benefit of NA therapy is lost among patients who develop NA resistance [5]. The emergence of NA-resistant mutations may lead subsequently to a loss of histologic improvement and, in some cases, severe exacerbations of liver diseases [6,7].…”
Section: Introductionmentioning
confidence: 99%